1992
DOI: 10.1111/j.1365-2052.1992.tb00144.x
|View full text |Cite
|
Sign up to set email alerts
|

The sequence of porcine αs1‐casein cDNA: evidence for protein variants generated by altered RNA splicing

Abstract: A cDNA library was constructed from mRNA isolated from lactating porcine mammary gland and screened with a bovine asl-casein cDNA clone. Three classes of cDNA isolated varied in the number of bases within the coding region. The full length porcine asl-casein cDN'4 is 1124bp and codes a preprotein of 206 amino acids. The other two classes of a,l-casein cDNA lacked 18 bp and 60 bp respectively when compared to the 1124-bp cDNA sequence. PCR amplification confirmed the presence of these sequences in total RNA. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Similarly, missing of exon 4 in bovine CSN1S1*A (Mohr, Koczan, Linder, Hobom, & Erhardt, 1994) and of exon 7 respectively exon 8 in ovine CSN1S1*I respectively CSN1S1*H (Giambra et al, 2010a(Giambra et al, , 2010b, were also reported. Beside exon skipping as a reason for casein alleles as described above, simultaneous occurrence of skipped and non-skipped forms of the same CSN1S1 allele are usual in sheep, goat, cattle, pig, and human (Alexander & Beattie, 1992;Ferranti et al, 1998;Johnsen, Rasmussen, Petersen, & Berglund, 1995;Leroux, Mazure, & Martin, 1992). Within ovine a s1 -CN alleles A, C, and D, for example, the appearance of at least eight protein forms, not related to allelic variability is described (Ferranti et al, 1995;2001;Ferranti, Lilla, Chianese, & Addeo, 1999), whereas 16.9% of whole a s1 -CN is missing exon 16 (Ferranti et al, 1998).…”
Section: Pcr-nomentioning
confidence: 92%
“…Similarly, missing of exon 4 in bovine CSN1S1*A (Mohr, Koczan, Linder, Hobom, & Erhardt, 1994) and of exon 7 respectively exon 8 in ovine CSN1S1*I respectively CSN1S1*H (Giambra et al, 2010a(Giambra et al, , 2010b, were also reported. Beside exon skipping as a reason for casein alleles as described above, simultaneous occurrence of skipped and non-skipped forms of the same CSN1S1 allele are usual in sheep, goat, cattle, pig, and human (Alexander & Beattie, 1992;Ferranti et al, 1998;Johnsen, Rasmussen, Petersen, & Berglund, 1995;Leroux, Mazure, & Martin, 1992). Within ovine a s1 -CN alleles A, C, and D, for example, the appearance of at least eight protein forms, not related to allelic variability is described (Ferranti et al, 1995;2001;Ferranti, Lilla, Chianese, & Addeo, 1999), whereas 16.9% of whole a s1 -CN is missing exon 16 (Ferranti et al, 1998).…”
Section: Pcr-nomentioning
confidence: 92%
“…The Role of Lactoferrin in Gastrointestinal and Immune Development and Function: A Preclinical Perspective lactoferrin contains 684 amino acids and shares 71.1% overall amino acid sequence identity with hLF. 74,75 Lactoferrin contains 1-4 glycans at asparagine (Asn) residues 233, 368, 476, and 545, depending on the species. 76 Glycans present in bLF include N-acetyllactosamine, N-acetylglucosamine, galactose, fucose, mannose, and n-acetylneuraminic acid.…”
Section: Volume 173s June 2016mentioning
confidence: 99%
“…76 Less is known about the glycosylation of porcine lactoferrin, but it appears to have a glycosylation site at Asn472 and possibly Asn365. 74 The N-glycans on hLF are comprised of sialylated and fucosylated complex-type structures, and many contain Lewis(x) epitopes. 77 Barboza et al 78 characterized the glycosylation of hLF in the milk of 5 mothers of the first 10 weeks of lactation by mass spectroscopy.…”
Section: Volume 173s June 2016mentioning
confidence: 99%